OMTI All-Sky Imager Quick-Look Data (OI emission, 557.7nm, 5s) at Tromso, Norway. - Kazuo Shiokawa; Yuichi Otsuka; ISEE IUGONET Metadata Management Group (名古屋大学, 2017)
Optical Mesosphere Thermosphere Imagers (OMTI) All-Sky Imager Quick-Look Data of OI emission taken with the 557.7nm filter at Tromso, Norway. dataset